Integrated Science (Double Award) Syllabus June 1985 - Caribbean Examinations Council (Caribbean Examinations Council, 1985)
The syllabus aims are set out under three headings: 1. Cognitive Skills 2. How science operates 3. Application and social awareness
Keywords: CXC syllabus